2007
DOI: 10.1302/0301-620x.89b2.18116
|View full text |Cite
|
Sign up to set email alerts
|

Unicameral bone cysts

Abstract: Open surgery is rarely justified for the initial treatment of a unicameral bone cyst, but there is some debate concerning the relative effectiveness of closed methods. This study compared the results of steroid injection with those of autologous bone marrow grafting for the treatment of unicameral bone cysts. Between 1990 and 2001, 30 patients were treated by steroid injection and 28 by grafting with autologous bone marrow. The overall success rates were 86.7% and 92.0%, respectively (p>0.05). The success rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 33 publications
(26 reference statements)
3
35
1
Order By: Relevance
“…Limitations: Our study population is comparable to other studies regarding age, gender ratio and incidence of pathologic fractures [18,39-41]. Like all retrospective studies, the study has certain limitations, e.g.…”
Section: Discussionsupporting
confidence: 56%
“…Limitations: Our study population is comparable to other studies regarding age, gender ratio and incidence of pathologic fractures [18,39-41]. Like all retrospective studies, the study has certain limitations, e.g.…”
Section: Discussionsupporting
confidence: 56%
“…(25) reported 94% success after 2-5 injections at two month intervals. In a study retrospectively comparing steroid injections with bone marrow injections, Cho et al (3) achieved 86.7% success with 1-6 injections over a 4-23 month period. Pavone et al (21) reported 65.2% success after 2-5 injections within a 2-6 month period.…”
Section: Discussionmentioning
confidence: 99%
“…The majority form in the childhood period (4-10 years) and are localized on the metaphysis of the long bones (3) . The most common locations are proximal humerus and proximal femur (4) .…”
Section: Introductionmentioning
confidence: 99%
“…Although their etiology is unknown, the venous obstruction theory is one of the most accepted models [14,15]. Selected cases, dependent on the location and size of the cyst, may require prophylactic treatment in order to prevent fracture and related complications.…”
Section: Discussionmentioning
confidence: 99%